PCF-based Multi-wavelength Laser using Four-wave Mixing Effect - Ahmad, Harith (De Gruyter, 2010)
A multi- wavelength comb is demonstrated using a four-wave mixing effect in a linear cavity resonator consisting of photonics crystal fiber (PCF) and a bi-directionally pumped Bismuth-based Erbium Doped Fiber (BiEDF). The comb is generated in 1585 nm region with assistance of the pump signal from Tunable Laser Source (TLS) with a line spacing varies from 0.34 to 0.39 nm. A stable output laser comb of 14 lines is obtained using a 80/20 coupler to inject the TLS signal and a total 1480 nm pump power of 270 mW.